Instrumental validity and intra/inter-rater reliability of a novel low-cost digital pressure algometer - Daniel Jerez-Mayorga; Carolina Fernanda dos Anjos; Maria de Cássia Macedo; Ilha Gonçalves Fernandes; Esteban Aedo-Muñoz; Leonardo Intelangelo; Alexandre Carvalho Barbosa (PeerJ, 2020)
Background Pain assessment is a key measure that accompanies treatments in a wide range of clinical settings. A low-cost valid and reliable pressure algometer would allow objective assessment of pressure pain to assist a variety of health professionals. However, the pressure algometer is often expensive, which limits its daily use in both clinical and research settings. Objectives This study aimed to assess the instrumental validity, and the intra- and inter-rater reliability of an inexpensive digital adapted pressure algometer. Methods A single rater applied 60 random compressions on a force platform. The pressure pain thresholds of 20 volunteers were collected twice (3 days apart) by two raters. The main outcome measurements were as follows: the maximal peak force (in kPa) and the pressure pain threshold (adapted pressure algometer vs. force platform). Cronbach’s α test was used to assess internal consistency. The standard error of measurement provided estimates of measurement error, and the measurement bias was estimated with the Bland–Altman method, with lower and upper limits of agreement. Results No differences were observed when comparing the compression results (P = 0.51). The validity and internal intra-rater consistencies ranged from 0.84 to 0.99, and the standard error of measurement from 0.005 to 0.04 kPa. Very strong (r = 0.73–0.74) to near-perfect (r = 0.99) correlations were found, with a low risk of bias for all measurements. The results demonstrated the validity and intra-rater reliability of the digitally adapted pressure algometer. Inter-rater reliability results were moderate (r = 0.55–0.60; Cronbach’s α = 0.71–0.75). Conclusion The adapted pressure algometer provide valid and reliable measurements of pressure pain threshold. The results support more widespread use of the pressure pain threshold method among clinicians.